Le travail et les métiers dans la télé-réalité : éléments pour une approche sociologique - Marc Perrenoud (Images du Travail, Travail des Images)
This paper deals with representations of work, industrial relations and occupational groups in TV shows, particularly in reality TV. The first part of the text gives a quick overview of the different types of TV programs (serials, documentaries, etc.) and of the way that work as a topic has been adressed for about thirty years. The second part examines in detail two reality TV shows in particular (Ramsey’s Kitchen Nightmares and Undercover Boss) to show how they produce a very normative and conservative discourse on work and industrial relations.